Pengembangan E-Modul Pembelajaran IPA berbasis Problem Based Learning untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - Yayuk Kaniyah; Iin Purnamasari; Joko Siswanto (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The purpose of this development research is to determine the feasibility, practicality, and effectiveness of problem-based learning e-science learning modules in improving the scientific literacy skills of Five Grades students at SDN Kalisalak 02 Limpung. This study is research and development by modifying the 4-D model (Four D model) from Thiagarajan. 4-D development through 4 stages, namely identification (define), planning (design), development (develop) and dissemination (dessiminate). The data collection instruments in this study were validity sheets for material expert lecturers, media experts and practitioners, student readability sheets, practicality sheets for practitioners, lesson plans validation sheets, scientific literacy questions validation sheets, scientific literacy pretest and posttest questions. This instrument was developed based on the review of supervisors, assessments of expert lecturers, practitioners, and limited trials on students and practitioners. The stage of implementing the e-module developed for Five Grades students at SDN Kalisalak 02 Limpung. The dessiminate stage is the stage of using e-modules that have been developed on a wider scale, through the website address for problem-based learning e-modules that have been online so that they are spread through Google and can be accessed in a browser. The data analysis technique used is the n-gain test and T test. The n-gain test value in this study was obtained by 0.32 with a moderate increase category, and the T test value obtained by Sig. 0.033 <0.05 means that there is an effect of using problem-based learning e-science learning modules to improve students' scientific literacy skills. The results showed that the problem-based learning-based science learning e-module that was developed was proven to be valid, practical, and effective so that it was very feasible to be used in science learning in elementary schools to improve students' scientific literacy skills.